The Effects of Nursing welcome program on the level of Stress and Satisfaction of patients in the Coronary Care Unit - Shahla Biglar; Abolhassan Rafiee; Maryam Puryaghoob; Fariba Sharafi; Fatemeh Moghaddam; Zahra Nisari (Golestan University of Medical Sciences, 2019)
Background: The management of Psychological symptom in patients and nurses, effective communication with patients are important issues that should be taken into consideration in nursing care. This study aimed to examine the effects of nursing welcome program on the level of stress and satisfaction in patients in the Coronary Care Units (CCU). Methods: The interventional study was done on 72 patients, who were admitted to CCU at Emdadi hospital in Abhar in 2017. The patients were selected by convenience sampling and were allocated into intervention (n= 36) and control (n= 36) groups. Data was collected using a questionnaire including demographic; Depression, Anxiety and Stress Scale (DASS-21), and the La Monica-Oberst Patient Satisfaction Scale (LOPSS). The DASS-21 was fulfilled by a welcome nurse through interview in both groups. Then the welcome nurse began to implement the Nursing Welcome Program in the intervention group. The level of patients' stress and satisfaction were measured an hour and 24 hours after the intervention respectively. Patients in the control group received routine care without any intervention. Data was analyzed using independent t-test, chi-square test, and Fisher's exact test in SPSS-16. Results: The Mean±SD of stress in intervention and control groups after intervention were 8.23±3.24 and 11.9±4.20 respectively (p= 0.001). The Mean±SD of satisfaction in intervention and control groups after intervention were 249.26±26.7 and 236.10±23.71 respectively (p=0.031). Conclusions: According to the importance of nurses' position in communicating with patients, employing welcome nurses as an effective care method to reduce psychological symptoms and increase patients' satisfaction is suggested.